Formal hepatitis C education enhances HCV care coordination, expedites HCV treatment and improves antiviral response. (20th March 2013) - Lubega, Samali; Agbim, Uchenna; Surjadi, Miranda; Mahoney, Megan; Khalili, Mandana
Abstract Background & Aims Formal Hepatitis C virus (HCV) education improves HCV knowledge but the impact on treatment uptake and outcome is not well described. We aimed to evaluate the impact of formal HCV patient education on primary provider‐specialist HCV comanagement and treatment. Methods Primary care providers within the San Francisco safety‐net health care system were surveyed and the records of HCV‐infected patients before and after institution of a formal HCV education class by liver specialty (2006–2011) were reviewed retrospectively. Results Characteristics of 118 patients who received anti‐HCV therapy were: mean age 51, 73% males and ~50% White and uninsured. The time to initiation of HCV treatment was shorter among those who received formal education (median 136 vs 284 days, P < 0.0001). When controlling for age, gender, race and HCV viral load, non‐1 genotype (OR 6.17, 95% CI 2.3–12.7, P = 0.0003) and receipt of HCV education (OR 3.0, 95% CI 1.1–7.9, P = 0.03) were associated with sustained virologic treatment response. Among 94 provider respondents (response rate = 38%), mean age was 42, 62% were White, and 63% female. Most providers agreed that the HCV education class increased patients' HCV knowledge (70%), interest in HCV treatment (52%), and provider‐patient communication (56%). A positive provider attitude (Coef 1.5, 95% CI 0.1–2.9 percent, P = 0.039) was independently associated with referral rate to education class. Conclusions Formal HCV education expedites HCV therapy and improves virologic response rates. As primary care provider attitude plays a significant role in referral to HCV education class, improving provider knowledge will likely enhance access to HCV specialty services in the vulnerable population.